Stability of Resistance to Imidacloprid in the Brown Planthopper (Nilaparvata lugens Stål.) from Banyumas, Central Java - Danarsi Diptaningsari; Y. Andi Trisyono; Aziz Purwantoro; Arman Wijonarko (Universitas Gadjah Mada, 2020)
Imidacloprid is one of the insecticides that has been widely used to control the brown planthopper (Nilaparvata lugens Stål.). The excessive use of insecticides led to the development of insecticide resistance in N. lugens. This study was aimed to determine the stability of resistance to imidacloprid in N. lugens from Banyumas, Central Java Province. The five generations of selection increased the resistance ratio (RR) from 46.20-fold to 150.39-fold. To assess the stability of resistance to imidacloprid in N. lugens, the fifth generation was further reared for 10 generations without exposure to insecticides. The stability studies showed that resistance to imidacloprid was unstable with a decrease of resistance from 150.39-fold to 38.14-fold after 10 generations without selections. Continuous selections with imidacloprid for three generations could increase the resistance level from 150.39-fold to 216.13-fold. The unstable resistance could be managed by removing the selection pressure for a period of time or switching to insecticides with different mode of actions. Information regarding resistance stability would be useful to determine an effective resistance management strategies in N. lugens.